2023
DOI: 10.1021/acs.energyfuels.2c04270
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Two-Dimensional Gas Chromatography: A Universal Method for Composition-Based Prediction of Emission Characteristics of Complex Fuels

Abstract: Liquid fuels such as gasoline, kerosene, or diesel exhibit a very complex chemical composition. The transition toward a sustainable world requires the development of novel alternatives to fossil-based light and middle distillates, leading to a further increase in the composition complexity by the introduction of chemical structures absent in fossil fuels. The transfer of fundamental knowledge on molecular behavior in combustion demands in the first place a reliable analysis of the composition of such fuels, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
(209 reference statements)
0
4
0
Order By: Relevance
“…Figure 5 shows the results for the fits with significant parameters used in the fitting operation. The standard errors of these fits are less than 0.01 cm 3 •mol −1 .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Figure 5 shows the results for the fits with significant parameters used in the fitting operation. The standard errors of these fits are less than 0.01 cm 3 •mol −1 .…”
mentioning
confidence: 81%
“…Nonane is a component of petroleum-based and alternative fuels and has been shown to make up approximately 9 mass % of Fischer–Tropsch crude oil . Its importance in fuel research is illustrated by its inclusion in pyrolysis and oxidation kinetic models for fuels and by studies that have investigated its combustion behavior alone and with other fuel components, such as methylcyclohexane and methyl octanoate. Many studies have explored the interaction of other linear alkanes found in fuel with alkylcyclohexanes through measurements of density, viscosity, and speed of sound, but very few measurements have been made for nonane. ,, Density and viscosity values have been measured for mixtures of nonane with methylcyclohexane up to 308.15 K, , n -butylcyclohexane up to 313.15 K, and adamantane derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rich abilities of the presented method, it is worth mentioning its drawbacks, which should be considered during routine analysis. One difficulty is distinguishing between compounds of similar classes on the chromatogram that all elute at the same time [ 18 ]. The other difficulty arises from the expensive running costs of GC×GC, which may not be efficient for analyzing a small number of samples.…”
Section: Methods Landscapementioning
confidence: 99%
“…Novel technical fuels consist of complex chemistry, involving many components in varying compositions [17]. To allow the chemical kinetic combustion modeling of novel fuels and their components, new reaction mechanisms need to be developed, or rather existing ones need to be extended.…”
Section: Introductionmentioning
confidence: 99%